Use of Differentized Learning Strategies to Improve Learning Outcomes of Class IV Students SDN Bumirejo 02 - Sazali, Mochamad Waluyo Anwar; Mayasari, Ruhana; Ningrum, Ary Setya Budhi; Tsani, Iskandar; Zuroidah, Ninik; Wahyuni, Sri (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This research uses a qualitative approach with a classroom action research model. The research subjects were class IV students at UPT SD Negeri Bumirejo 02 for the first time. Observations in cycle II learning activities obtained data in the form of the results of implementing Islamic Religious Education learning and student learning outcomes consisting of aspects of knowledge and attitudes during the learning activities. The results obtained during the research were followed by a discussion of the research results on the learning process, a general conclusion was obtained, namely, that implementing the use of differentiated learning strategies can improve the learning outcomes of class III students in learning Islamic Religion on prophets and apostles material, this is proven by the percentage of students completing after cycle II increasing to 90.13%. The suggestion that researchers give is that teachers are expected to use this strategy which is adapted to the situation and conditions so that learning is more interesting and easy for students to understand.